Analisis Wacana Digital Penggunaan Verbal Abuse dalam Konten Gameplay Stumble Guys Luthfi Halimawan - Muhammad Usamah Robbani; Heidy Arviani; Syafrida Febriyanti (Peneliti.net, 2023)
This study discusses the discourse contained in Luthfi Halimawan's YouTube uploads in playing the game